The Metamorphosis of Alexandru Resmeriță. Drawing Professor, Linguist, “Iron Guard Priest”? - Bronwyn Cragg (Plural: History, Culture, Society)
This article provides a biography of Alexandru Resmeriță (1866–?), a drawing teacher from Turnu-Severin. It traces Resmeriță’s early nationalistic writings before and after the First World War, and his transformation into an amateur linguist and early “Dacomaniac”. It discusses media response to his linguistic theories, and shows how his proposed Latin etymologies were influenced by his nationalism. Further, it examines his involvement in A.C. Cuza’s antisemitic League for National-Christian Defense (Liga Apărării Național-Creștine), and Resmeriță’s publication of antisemitic texts during the interwar period. Finally, it shows that, through overuse, misattribution, and misunderstanding of a single anecdote, Resmeriță’s name was spread throughout English-language Holocaust historiography, described as a prominent antisemitic or fascist theorist, as an Orthodox priest, or as a member of the Iron Guard. It argues that these assessments are variously incorrect, and analyses how the citation was spread and misinterpreted by historians in different secondary sources.